Expression of Cultural Resistance in Rajan Mukarung’s Poetry - Timalsina, Ramji (Dristikon: A Multidisciplinary Journal, 2019)
What is the value of using ethnic culture in literature written in the mainstream language? For whose benefit is it done so? Rajan Mukarung’s latest collection of poems entitled Haataa Jaane Aghillo Raat [The Night Before the Market Day] (2076BS/ AD2019) has shown that it is a strategy of cultural resistance of the marginalized culture against the dominant one. This article is an attempt to show how the marginalized group in a nation can resist the mainstream politics and culture with the use of ethnic culture and deconstruction of the mainstream one in their literary creations. The themes and styles in poetry can show both the representation of the life guided by the subculture and resist the dominance of the next. For this, the theory of cultural resistance developed and used by Michel Foucault, Stuart Hall and Chris Barker has been used. The analysis is based on the interpretation of Mukarung’s poems.